Quality management systems in geodesy - Boris Tundzev; Zlatko Bogdanovski; Zlatko Srbinoski (Geodetic Faculty, Zagreb, Croatia, 2015)
Implementing systems of quality management in modern geodetic organizations should be a strategic decision that will ensure the monitoring of changes in the environment, realizing the needs and achievement of objectives, quality of service and uniformity of processes in the organization. The classic approach provides in the first stage of implementation to implement the system of quality management ISO 9001 QMS (Quality Management Systems), and then to implement any else's management system. Opposite of that, modern approach and recent practical experience preferred implementation of integrated management systems - IMS (Integrated Management System). IMS is the best system that simultaneously satisfies the users of services, restructuring the company, reduce costs, increase productivity and profits as well as long term development and effective way of the company managing. In this paper is elaborated principle and strategy for the integration of basic IMS (ISO 9001 Quality Management Systems - QMS, ISO 14001 Environmental Management Systems - EMS, and OHSAS 18001 Occupational Health & Safety Assessment Series) in process management of geodetic companies. IMS politics should be incorporated into overall business strategy of the geodetic company, in order for permanent improving the work quality of the company, protection and improvement of the environment, maintenance and continuous improvement of health protection and safety at work. Standards for quality management provide a wide range of benefits of economic, technological and social aspect in the organization - internal and external benefits in the overall business environment
Keywords: geodetic companies, International organization for standardization (ISO), Integrated management systems (IMS), Quality management system (ISO 9001 QMS), Environmental management system (ISO 14001 EMS), Occupational health and safety assessment series management systems (OHSAS 18001)